Home accidents among elderly patients. The role of the GP in prevention and mitigation of their consequences - Manasterski, Szymon; Mastalerz-Migas, Agnieszka (Lekarz POZ, 2016)
Home falls are one of the major causes of deterioration of the quality of life or death among people over 65-years of age. Among all causes of deaths in this age group, half of them are falls occurring at home. Fall can be one of the worst injuries in the life of an elderly person, especially among women. These events often lead to a complete reorganization of life and irreversible health, psychological and social effects. Risk factors contributing to accidents are divided into biological, behavioural, environmental and socio-economic category. GPs have a special role in reducing the incidence of falls among people over 65 years old. With the help of the HOME FAST scale and cooperation with occupational therapists they may reduce the incidence of falls and their consequences among their patients.